Plant trait–environment relationships in salt marshes: Deviations from predictions by ecological concepts - Minden, Vanessa; Andratschke, Sandra; Spalke, Janina; Timmermann, Hanna; Kleyer, Michael (Perspectives in plant ecology, evolution and systematics, 2012)
Salt marshes are exposed to high groundwater levels and salinity due to periodical inundation and are under constant influence of physical disturbance. Plants inhabiting salt marshes need to pursue different strategies to colonize this environment and hence, trait expressions should vary along the elevation gradient from pioneer zone to upper salt marsh. We verified various trait–environment concepts for their applicability to different salt marshes zones, and found some are opposite to that of other terrestrial plants. We used RLQ to analyse the joint structure between environmental conditions (R-table) and species traits (Q-table) by use of a species abundance table (L-table). RLQ analyses the inertia of scores of R- and Q-table linked by species scores of L-table. Then we clustered species according to their position along the RLQ axes to form functional groups. The ‘physiological–ecological–amplitude’ concept could not be confirmed from the trait perspective, as the species of the ‘stressful’ lower marsh show trait values indicating higher competitive ability (canopy height and stem mass fraction) than those of the ‘benign’ upper parts. Also, specific leaf area (SLA) and leaf dry matter content (LDMC) of salt marsh plants were more constrained by a salt–waterlogging gradient than by a nutrient gradient. This is opposite to the leaf economics spectrum, which describes a trade-off from fast growing species with the potential of quick return of investments of nutrients to species with long leaf lifetime and low rates of photosynthesis. Our results are consistent with the theory of functional equilibrium and Tilman's allocation model, which is a shift in allocation to plant organs responsible for capturing limiting resources resulting in higher fractions of that organ relative to the whole plant body.